2019
DOI: 10.2196/12165
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Literacy, Electronic Health Literacy, Disease-Specific Knowledge, and Health-Related Quality of Life Among Adults With Chronic Obstructive Pulmonary Disease: Cross-Sectional Study

Abstract: Background Despite the relatively high prevalence of low health literacy among individuals living with chronic obstructive pulmonary disease (COPD), limited empirical attention has been paid to the cognitive and health literacy–related skills that can uniquely influence patients’ health-related quality of life (HRQoL) outcomes. Objective The aim of this study was to examine how health literacy, electronic health (eHealth) literacy, and COPD knowledge are associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…It has been defined as “the ability to seek, find, understand, and appraise health information from electronic sources and to apply the knowledge gained to addressing or solving health problems [ 35 ].” eHealth literacy is becoming increasingly important as individuals continue to seek medical advice from various web-based sources, especially social media. Empirical studies have also found that eHealth literacy positively influences health outcomes, such as health-promoting behaviors among people with diabetes [ 36 ] and people’s health-related quality of life [ 37 ]. College students with higher eHealth literacy were found to be less likely to consume unhealthy food [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been defined as “the ability to seek, find, understand, and appraise health information from electronic sources and to apply the knowledge gained to addressing or solving health problems [ 35 ].” eHealth literacy is becoming increasingly important as individuals continue to seek medical advice from various web-based sources, especially social media. Empirical studies have also found that eHealth literacy positively influences health outcomes, such as health-promoting behaviors among people with diabetes [ 36 ] and people’s health-related quality of life [ 37 ]. College students with higher eHealth literacy were found to be less likely to consume unhealthy food [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A mediation analysis by Schulz et al [ 25 ] found that eHealth literacy is weakly associated with health system utilization, though the premise of health literacy resembles eHealth literacy. Additionally, low eHealth literacy is associated with poor quality-of-life outcomes in patients with chronic lung disease [ 34 ]. Another research group found that mHealth apps users with heart disease or diabetes have a higher level of eHL [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, health literacy has not yet been shown to accurately serve the needs of patients with diabetes who rely heavily upon the internet and mobile technology. An eHL measure [ 22 , 34 ] merely reflects internet use without specifically covering mobile apps. Also, the eHL measure has been questioned because it only reflects individuals' perceived performance of online tasks without necessary objective reports [ 31 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COPD suffer from physiological problems due to the decline in lung function, such as breathlessness, expectoration, and coughing (Global Initiative for Chronic Obstructive Lung Disease, 2020). Exacerbation in COPD leads to economic burden, frequent hospitalization, and complications (Lisspers et al., 2018; Overington et al., 2014; Stellefson, et al., 2019). Moreover, diagnosis and treatment of COPD have widely negative effects on the patients’ mental health, including depression and anxiety (Economou et al., 2018).…”
Section: Introductionmentioning
confidence: 99%